Fourier Transform Infrared (FTIR) spectroscopy, gas chromatography and chemometric analysis for halal authentication in food products - Nazri, Muhammad Zulhelmi; Abd Rashid, Siti Nor Azlina; Abang Zaidel, Dayang Norulfairuz (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The increasing of worldwide demand for halal-certified food products warrants the robust analytical methods to ensure compliance with Islamic dietary laws. Conventional verification methods are insufficient to detect non-halal components in complex food matrices, especially the processed food products. This article explores the integration of Fourier transform infrared (FTIR) spectroscopy, gas chromatography (GC) and chemometric analysis as advanced and comprehensive tools for halal authentication. The FTIR spectroscopy offers rapid, non-destructive analysis of food samples while GC provides precise compositional profiling of fatty acids and volatile compounds, respectively. When the FTIR and GC data coupled with multivariate statistical approaches as such principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA), these techniques enable the identification of prohibited substances, including lard and porcine gelatine, even at trace levels. Case studies demonstrate high accuracy in classifying halal and non-halal food products using spectral and the chromatographic data. Furthermore, the development of portable instrumentation and cloud-based chemometric platforms has expanded the practical applicability of these methods for real-time quality control in industrial and regulatory settings. This article underscores current advancement, challenges and future directions in analytical halal authentication, emphasising the potential of these integrated techniques to ensure food integrity across the global supply chain.